2012
DOI: 10.1111/j.1365-2842.2012.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of IGF1, IGFR1 and IGFBP3 in mandibular condylar cartilage between male and female rats applied with malocclusion

Abstract: This study was designed to investigate the expression differences of insulin-like growth factor-1 (IGF1), IGF type 1 receptor (IGFR1) and IGF-binding protein-3 (IGFBP3) in mandibular condylar cartilage between male and female rats with experimentally created malocclusion. A total of 40 male and 40 female rats were used, and malocclusion was created by moving the first molars mesially and the third molars distally in the experimental group. Animals were killed at the end of the second and fourth weeks. Haematox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…They suggested that IGF1 stimulates metatarsal longitudinal growth by increasing the proportion of proliferating cells in proliferative zone and enhancing of cell differentiation/hypertrophy in hypertrophic zone 29 . Likewise, during the process of cartilage degeneration, the expression of IGF1and IGF1R decreased in proliferative and hypertrophic zones in female SpragueeDawley rats 30 . BCL2, as a predominant antiapoptotic factor, was frequently used as a maker of cell survival by blocking apoptosis 9 .…”
Section: Discussionmentioning
confidence: 92%
“…They suggested that IGF1 stimulates metatarsal longitudinal growth by increasing the proportion of proliferating cells in proliferative zone and enhancing of cell differentiation/hypertrophy in hypertrophic zone 29 . Likewise, during the process of cartilage degeneration, the expression of IGF1and IGF1R decreased in proliferative and hypertrophic zones in female SpragueeDawley rats 30 . BCL2, as a predominant antiapoptotic factor, was frequently used as a maker of cell survival by blocking apoptosis 9 .…”
Section: Discussionmentioning
confidence: 92%
“…This suggests that although IGF-1 is more abundant in OA, it may not be bioavailable to exert its beneficial effects on cartilage. [16,31] Furthermore, increased local production of IGFBP-3 has been found in OA joints, [32] thus, further limiting the action of IGF-1 during the progression of the disease. [18] Development of treatment strategies that would either increase the levels of bioavailable IGF-1 and/or decrease the local production of IGF-binding proteins may be beneficial to restore homeostasis in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Artificially reducing circulating levels of IGF in transgenic mice causes a 30% reduction in body size compared to control littermates . Studies in a broader range of species show circulating IGF levels correlating positively with growth differences, including dog breeds , rats , several species of fish , as well as snakes , ducks , and humans .…”
Section: Insulin/insulin‐like Signaling (Ils) Pathways and Condition‐mentioning
confidence: 99%